Influence des changements d’utilisation des terres sur les débits du bassin versant du Massili à Gonsé (Burkina Faso) - Bagré Mathias Philippe; Yonaba Roland; Sirima Badaye Abdoulaye; Somé Yelezoumin Stephane Corenthin (VertigO)
This study aims to determine the contribution of land use changes on runoff in the Massili basin in Gonsé. The study methodology is based on the analysis of the temporal variability of rainfall (1975-2019) and discharge (1975-2019) and the diachronic analysis of land use (1975-1991-2007-2019). The statistical tools used are Pettitt’s test, Hubert’s segmentation procedure, Mann-Kendall test and Pearson’s correlation test. The results show that the Massili catchment area experienced a long dry period from 1975-2001 and a wet phase from 2002-2019. The breakpoint detection test highlighted changepoints in 2002 and 2003 (Pettitt), 2004, 2008 and 2019 (Hubert’s segmentation) with increase ranging from 64,55% to 95,76% after the breaks. Significant upward trends were observed for monthly and annual flows. The Pearson test reveals a low correlation between rainfall and discharge with values between 0,141 and 0,225. These findings show that the evolution discharge is affected by the regression rate of the savannahs of -79,69% and riparian formations of -14,84%, to the benefit for urban areas of 1006,65%, the bare soil of 388,92% and agricultural area of 79,92%, favorable to runoff. The results shed light on the causes of streamflow variability and might be useful in framing integrated land and water resources management policies.